Análise palinológica de amostras de mel de Apis mellifera L. produzidas no estado de Sergipe, Brasil - Silva, Ana Paula Conceição (2012)
In this work it was conduced a palynological investigation of honey produced in the state of Sergipe, with the objective of delineating a botanical and geographical profile of the honey. The melissopalynological analyses were made using samples from 22 municipalities in the State, coming from honey producers and cooperatives. The methodology employed in the preparation of the honey samples was the usual in melissopalynology with the use of acetolysis. Whenever possible, the pollen grains were identified with the aid of specialized literature and by comparison with the reference pollen collection of the Plant Micromorphology Laboratory (LAMIV-UEFS). A total of 500 pollen grains were counted from each sample in order to obtain the frequency class of each pollen type. Lycopodium clavatum spores were included to obtain the pollen concentration of the honey samples. The results of the research are presented in two chapters. The first chapter presents a palynological characterization of the Apis mellifera L. honey samples produced in Sergipe, with 22 samples analyzed from different municipalities originating in the eight territories that compose the state. A total of 90 pollen types were identified, which were distributed in 28 plant families. The family with highest diversity of pollen types was Fabaceae with 29 types, followed by Asteraceae (8), Rubiaceae (7), Anacardiaceae and Malvaceae (4 each), and Euphorbiaceae and Myrtaceae (3 each). Pollen types from the genus Mimosa displayed high representativity in the pollen spectrum of the state, with 14 pollen types, being found at all municipalities sampled. Regarding the absolute pollen concentration, the honey samples analyzed displayed a remarkable a low concentration, with 23.8% of the samples placed in category I (<20,000 pollen grain in 10g of honey) and 61.9% of the samples places in category II (20,000-100,000). The second chapter presents the results of a study focused at the Alto Sertão Sergipano territory, in the semiarid region of the state, from which a total of 20 honey samples from five municipalities were analyzed. A total of 72 pollen types belonging to 26 families were detected in the honey samples analyzed. The most diverse family in number of pollen types was Fabaceae with 23 types, followed by Asteraceae (10), Rubiaceae (7) and Euforbiaceae (4). The participation of pollen types related to the genus Mimosa (Fabaceae) was prominent in the composition of the honey in the region investigated. A low concentration of pollen grains was evident in the honey samples analyzed, with 68.4% placed in category I and 26.3% in category II. The richness of pollen types found in the honey samples from the state of Sergipe makes evident the diversity of floral resources employed by Apis mellifera in the region and high potential for the production of honey organic of the State.